Analisis Penerapan Model Pembelajaran Project Based Learning Berbasis Content Video Pada Pembelajaran Konsep Dasar Sains Mahasiswa - Raras Setyo Retno (Program Studi Pendidikan Guru Sekolah Dasar, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Malang, 2022)
The project-Based Learning (PjBL) model is a learning model that identifies, through research, real-world problems, from local to global, and develops solutions using evidence to support claims, offers solutions using multimodal approach to a presentation based on a set of 21st century skills. This research aims to analyze the application of the Project-Based Learning (PjBL) model based on video content in learning the basic concepts of science for students. This descriptive research uses phenomenological approach, which is a study that describes the meaning of individuals regarding their experience of a concept or phenomenon. The data collection techniques are conducted through observation, interviews, and documentation. The interactive analysis model from Matthew B Miles and Hubermen is used for data analysis. The model technically consists of 4 (four) main phases: data collection, data reduction or simplification, data presentation, and conclusion or verification. The analysis results show that the implementation of the PjBl learning model is effective, as seen from the students activities which closely complies to the steps. In addition, students are more creative, active, and innovative in learning science and show more confidence. Students are also more independent in learning about the topic they are interested in and becoming tutors for their friends